Malay folk choral music: Selected works of Juliette Lai Sau Kuen and Geneviene Wong Jen Pei / Lee Siew Pui - Lee, Siew Pui (2015)
The amalgamation of the choral idiom and folk music began in Europe in the nineteenth-century alongside the propagation of romantic nationalism, public enlightenment and folk revival. From early twentieth-century onwards, the phenomenon of folk choral music and its ideologies emerged in many non-European countries including Malaysia later on. Many scholars relate the development and revival of folk music in Europe, largely by arranging folk music into part-songs or choral arrangements, to Romantic nationalism in the 19th century. However, there is a lack of attention paid to folk choral music and its contexts in non-European countries especially in Asian countries, and in this research, concerns were given to the context of Malaysia. This research examines the Malay folk choral music, looking into its stylistic features, compositional style and performance practice based on a case study of selected Malay folk choral arrangements by Geneviene Wong and Juliette Lai. Methods include prefieldwork, fieldwork, and post-fieldwork. The different employment of folk elements in a Western choral setting, including those shown by data gathered from rehearsal sessions, performances, interviews with the composers and conductors, was analysed using scores. The results reveal four categories of folk music employment: musical borrowings, folk revival, hybridity, and appropriation for national music identity. These categories define the positioning of the folk element within the Malaysian folk choral setting where the Western hegemony is obvious. Hence, the outcome provides a thorough documentation of the stylistic feature, performance practice, interpretation of the selected repertory of Malaysian composers Lai and Wong.